The genomic landscape of malignant peripheral nerve sheath tumors: diverse drivers of Ras pathway activation. Issue 1 (December 2017) - Brohl, Andrew; Kahen, Elliot; Yoder, Sean; Teer, Jamie; Reed, Damon
Abstract Malignant peripheral nerve sheath tumor (MPNST) is an aggressive soft tissue sarcoma. To more fully characterize the genomic landscape of this tumor type, we performed next generation sequencing studies for mutational and copy number analysis. We analyzed whole exome sequencing data from 12 MPNST and SNP arrays for a subset of these. We additionally conducted a literature review of prior next generation sequencing studies in this disease and compared to the current study. We report recurrent mutations inNF1, SUZ12, EED, TP53 andCDKN2A in our study cohort. Combined with prior studies, we calculate the disease specific incidence of mutation in these genes to be:NF1 (56/64 = 87.5%).SUZ12 (69/123 = 56.1%), EED (40/123 = 32.5%), TP53 (29/72 = 40.3%), andCDKN2A (54/72 = 75.0%). Notably, we also identified frequent Ras pathway activating somatic mutations outside of these previously reported recurrently mutated genes. Five of the 12 MPNST in our cohort (42%) contained such a mutation. In conclusion, our study adds to the growing understanding of the genomic complexity of MPNST. We report a previously underappreciated frequency and variety of secondary or tertiary Ras pathway activating mutations, though not highly recurrent in a single gene.